Students’ perceptions towards the application of law and governance in education: regulations and legal rights - Zanariah, Nawawi; Hasmadi, Hassan (Universiti Malaysia Pahang, 2021)
There were several mainstream media coverages and court judgements that reported cases of educator misconduct and educational malpractice made by parents and students against educators for offences, involving incompetency in teaching, evaluation, negligent supervision, commission of criminal offences and impropriety with students. Thus, with the rise in court litigations involving educators and educational institutions the authority has taken a firm stand to resolve the issues. Students and educators share the conception that most all legal education develops students’ skills to argue and express their reason opinion, to collaborate and solve problems rationally, legal education promotes and strengthens a person’s respect of themselves and others, tolerance and responsibility. The neglect of children by parents and guardians are increasing in Malaysia despite the existence of legal provisions. The purpose of this study is to investigate the students’ knowledge towards law and governance in education. There were 100 forms which will be distributed for 50 Science Students and 50 Art Students. The questionnaires were divided into 5 sections. Section A is the students’ background, Section B is the students’ knowledge on aspects of negligence in school, Section C is the students’ knowledge on individual legal rights, Section D is the students’ knowledge on regulations and procedure related to school discipline and Section E is the students’ knowledge on corporal punishment.